2016
DOI: 10.22159/ajpcr.2016.v9s3.14576
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant Activity of Citrus Maximus Leaves in Experimental Animal Models

Abstract: Objective: To assess the anticonvulsant activity of ethanolic extract of Citrus maximus (EECM) leaves of maximal electroshock seizure (MES) and pentylenetetrazol (PTZ)-induced seizure models on albino (Wistar strain) rats and mice.Methods: Anticonvulsant activity was carried out by MES model and PTZ-induced clonic convulsions model; in each model, albino rats (Wistar strain) of either sex were taken and divided into five groups, each consisting of 6 rats. One group was used as control (3% w/v gum acacia), one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…There was complete abolition of the extensor phase in the standard group of phenytoin. From the above findings, it can be observed that the ethanolic leaf extract of R. tetraphylla reduced the extensor phase of convulsion in the dose-dependent manner [9,10] with maximum effect seen at the dose of 600 mg/kg. In PTZ model, the onset of extensor phase increases with an increase in dose from 200 to 600 mg/Kg body weight.…”
Section: Discussionmentioning
confidence: 96%
“…There was complete abolition of the extensor phase in the standard group of phenytoin. From the above findings, it can be observed that the ethanolic leaf extract of R. tetraphylla reduced the extensor phase of convulsion in the dose-dependent manner [9,10] with maximum effect seen at the dose of 600 mg/kg. In PTZ model, the onset of extensor phase increases with an increase in dose from 200 to 600 mg/Kg body weight.…”
Section: Discussionmentioning
confidence: 96%